Plan quinquenal de marketing para la empresa farmacia Cruz Azul de la ciudad de Nueva Loja, cantón Lago Agrio, provincia de Sucumbíos, para el año 2016 - Cholango Quinte, Rosa Omaira (2017)
The objective of this thesis was to elaborate a Quinquennial Plan of Marketing for the pharmacy Cruz Azul of the city of Nueva Loja; With the purpose of improving the economic and competitive development of the company since through the marketing plan we facilitate the efficient selection of any type of product or service. For that the different materials and methods were used: for the elaboration of the present work as the descriptive, inductive, deductive, statistical and analytical; While in terms of techniques the interview was conducted with the company manager, surveys directed at 358 external clients and 5 internal clients of the pharmacy. Next, a diagnosis was made of the Cruz Azul pharmacy, in which its history, its framework and micro location were determined. Later, an external analysis of the factors involved in the company was carried out, such as economic, political, technological And demographic, which allowed the detection of threats and opportunities that affect the company, which were weighted in order of priority. According to the analysis of the EFE and EFI matrices, it is determined that the EFE weighted factor is 2.6. This means that in the company there is a predominance of threats over opportunities, but can face the threats taking advantage of market opportunities, which allows Farmacia Cruz Azul of the city of Nueva Loja to develop without many setbacks within its environment. In relation to the EFI weighted factor, a value of 3 was obtained, which implies that the company has no internal problems. The conclusions and recommendations were then determined based on the analysis carried out at the company Cruz Azul, which are expected to be attended or performed by the Manager - Owner of the company mentioned above to achieve a better development and greater utility of the company . The implementation of the proposal will require a 5 year time and a budget of US $ 24552.56 and has to do especially with increasing the coverage of the company, increase sales, improve customer loyalty and improve the Customer service in the company.